Branching patterns in leaf starches from Arabidopsis mutants deficient in diverse starch synthases. (12th January 2015) - Zhu, Fan; Bertoft, Eric; Szydlowski, Nicolas; d'Hulst, Christophe; Seetharaman, Koushik
Graphical abstract: Highlights: Cluster structure of Arabidopsis leaf starch explored. Leaf starch in relation to storage starch structurally linked. Diverse starch synthases in relation to structure studied. Abstract: This is the first report on the cluster structure of transitory starch from Arabidopsis leaves. In addition to wild type, the molecular structures of leaf starch from mutants deficient in starch synthases (SS) including single enzyme mutants ss1-, ss2-, or ss3-, and also double mutants ss1-ss2- and ss1-ss3- were characterized. The mutations resulted in increased amylose content. Clusters from whole starch were isolated by partial hydrolysis using α-amylase of Bacillus amyloliquefaciens . The clusters were then further hydrolyzed with concentrated α-amylase of B. amyloliquefaciens to produce building blocks (α-limit dextrins). Structures of the clusters and their building blocks were characterized by chromatography of samples before and after debranching treatment. While the mutations increased the size of clusters, the reasons were different as reflected by the composition of their unit chains and building blocks. In general, all mutants contained more of a-chains that preferentially increased the number of small building blocks with only two chains. The clusters of the double mutant ss1-ss3- were very large and possessed also more of large building blocks with four or more chains. The results from transitory starch are compared with those from agriculturally important crops in the context that to what extent the Arabidopsis can be a true biotechnological reflection for starch modifications through genetic means.